2006
DOI: 10.1111/j.1365-2052.2006.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

The bovine fatty acid binding protein 4 gene is significantly associated with marbling and subcutaneous fat depth in Wagyu x Limousin F2 crosses

Abstract: Fatty acid binding protein 4 (FABP4), which is expressed in adipose tissue, interacts with peroxisome proliferator-activated receptors and binds to hormone-sensitive lipase and therefore, plays an important role in lipid metabolism and homeostasis in adipocytes. The objective of this study was to investigate associations of the bovine FABP4 gene with fat deposition. Both cDNA and genomic DNA sequences of the bovine gene were retrieved from the public databases and aligned to determine its genomic organization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
129
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 12 publications
2
129
3
6
Order By: Relevance
“…This hypothesis is supported by the following facts: the porcine FABP4 is closely associated to the FAT1 locus on chromosome 4, and the FAT1 has an important effect on meat marbling and growth (Mercadé et al, 2006). Furthermore, integrated analyses of both genetic map and radiation hybrid (RH) map indicated that the bovine FABP4 gene falls into the QTL interval for marbling on chromosome 14 (Michal et al, 2006). Interestingly, the same functional QTL has been detected on sheep chromosome 9, which is homologous to bovine chromosome 14 (Barillet et al, 2005).…”
Section: Discussionsupporting
confidence: 55%
“…This hypothesis is supported by the following facts: the porcine FABP4 is closely associated to the FAT1 locus on chromosome 4, and the FAT1 has an important effect on meat marbling and growth (Mercadé et al, 2006). Furthermore, integrated analyses of both genetic map and radiation hybrid (RH) map indicated that the bovine FABP4 gene falls into the QTL interval for marbling on chromosome 14 (Michal et al, 2006). Interestingly, the same functional QTL has been detected on sheep chromosome 9, which is homologous to bovine chromosome 14 (Barillet et al, 2005).…”
Section: Discussionsupporting
confidence: 55%
“…In fact, CEBPA and FABP4 mRNA levels in the SAT were increased in the fat pigs, without noticeable changes in the LL muscle. FABP4 protein level has been associated with pig's growth stage (Cho et al, 2011), backfat thickness (Michal et al, 2006) and IMF content . Moreover, FABP4 could be perceived as a marker for adipocyte number (Hocquette et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, this polymorphism was significantly associated with marbling and subcutaneous fat depth in Wagyu × Limousin F2 population (Michal et al, 2006) and in Korean native cattle (Cho et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A/G transition in the FABP3 gene described by Wu et al (2005); 4. G/C transversion in the FABP4 gene described by Michal et al (2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation